Liver transplantation in the Intensive Care Unit: twenty years experience in a center medium income on Peru - Cerron Cabezas, Carmen Ana (2021)
Liver transplantation is the major treatment for end-stage liver disease. Postoperative care is a great challenge to reduce morbidity and mortality in patients. In this sense, management in the liver ICU allows hemodynamic management, coagulation monitoring, renal support, electrolyte disturbances, respiratory support and early weaning from mechanical ventilation and evaluation of the liver graft. Objective: The present study shows the results of the management of liver transplant patients in 20 years of experience in a transplant center in a low- to middle-income country. Materials and methods: The medical records of 273 adult patients in the ICU in the immediate postoperative liver transplant were reviewed, from March 20, 2000 to November 30, 2020, including the effect of the pandemic caused by COVID-19. Liver-kidney, retransplanted, SPLIT, and domino transplant patients were excluded. Results: The most frequent etiology for LTx was NASH (35%), the mean age was 49 years, MELD Score ranged 15 - 20 (47.5%), 21 - 30 (46%) > 30 (6.2%). ICU pre transplant stay 7%, average ICU stay: 7.8 days. APACHE average admission: 14.9 points. Weaning extubation of 91.8% patients in ICU and Fast Track in 8.2%. The most frequent respiratory complication was atelectasis 56.3%, pneumonia (31.3%); AKI 1 (60.9%), and 11.1% with hemodyalisis support (AKI3). Immunosuppression: Tacrolimus (8.9%). Post-operative ICU mortality was 6.2%. Conclusions: The management of liver transplantation in the ICU is essential to achieve optimal results in patients who present advanced liver disease and require advanced life support in the immediate postoperative period and thus optimize graft survival.